KONSEPSI BIMBINGAN PRANIKAH DALAM PERSPEKTIF ISLAM DAN KRISTEN: ANALISIS BUKU KARYA QURAISH SHIHAB DAN JONAR SITUMORANG - Muhammad Nurullah Erfany; Totok Agus Suryanto (Yayasan Literasi Sains Indonesia, 2025)
The phenomenon of increasing divorce rates today shows that marriage is often no longer considered sacred by couples who are about to get married. One of the causes is the lack of understanding of premarital because they do not participate in premarital guidance programs. This study aims to examine the concept of premarital guidance from the perspective of two religious figures, namely Muhammad Quraish Shihab from Islam and Jonar Situmorang from Christianity, through a review of their two main works. This study uses a descriptive qualitative approach with a literature study method and content analysis techniques. The main books analyzed are Pengantin Al-Qur'an: 8 Nasihat Perkawinan untuk Anak-Anakku by Quraish Shihab and Berani Menikah by Jonar Situmorang. The results of the study show that premarital guidance according to Quraish Shihab emphasizes the importance of forming the personality of prospective couples, fairness in responsibility, openness of communication, role readiness, and economic stability. Meanwhile, Situmorang highlights the importance of the principle of the sanctity of Christian marriage through the wife's obedience, affection, understanding of the differences between partners, and the role of a wise husband and a capable wife. Both agreed that premarital guidance is an important provision in building a harmonious and sustainable household.